Dose-related effect of acetylcholine on human gingival blood flow - Tamás László Nagy; Barbara Mikecs; Zsolt M. Lohinai; János Vág (BMC, 2024)
Abstract Background This study investigates the dose-response relationship of acetylcholine (ACh) on healthy human gingival blood flow (GBF). Understanding this dose-response relationship contributes to studying vasodilatory mechanisms in various pathological conditions. Methods The study involved 22 young healthy men (21 - 32 years) to investigate the dose-response relationship of ACh on GBF. Semi-circular wells were created on the labial surface of the upper right second incisor (FDI #12) and upper left first incisor (FDI #21), including the gingival sulcus, for the application of drugs. ACh-chloride solutions at 0.1, 1, and 10 mg/mL were administered to the gingival sulcus of tooth FDI #12 with a Hamilton syringe. Physiological saline was applied on the contralateral side to FDI #21 as a control. The GBF was measured non-invasively by the laser speckle contrast imaging method in four 1mm high adjacent regions: coronal, midway1, midway2, and apical, and was expressed in a laser speckle perfusion unit (LSPU). After the baseline blood flow recording, ACh doses were applied sequentially, with washout periods in between. Data were statistically analyzed using a linear mixed model. Results The GBF did not change on the saline site throughout the experiment. The GBF was significantly higher at the coronal region after all ACh doses (baseline: 218±31 LSPU, and 227±38 LSPU p < 0.05, 239±40 LSPU p < 0.001, 291±54 LSPU p < 0.001, respectively) compared to the saline. It was also elevated following 1 and 10 mg/mL at the midway1 (245±48 LSPU, p < 0.05, 293±65 LSPU p < 0.001). At midway2 and apical, only the 10 mg/mL dose was effective (285±71 LSPU, p < 0.001; 302±82 LSPU, p < 0.001). Conclusions Our findings suggest a dose-dependent vasodilation to ACh, emphasizing its role in human gingival microcirculation. Only the 10 mg/mL ACh could evoke remote vasodilation 3 mm from the application. The described method could facilitate the investigation of endothelium-dependent vasodilation in disorders affecting microcirculation, such as periodontitis or diabetes.